Description of Ptychocroca, a new genus from Chile and Argentina, with comments on the Bonagota Razowski group of genera (Lepidoptera: Tortricidae: Euliini) - Brown, John W.; Razowski, Józef (Zootaxa, 2003)
Ptychocroca, new genus, is described and illustrated. As presently defined, the genus includes eight species: P. apenicillia, new species, from Chile; P. nigropenicillia, new species, from Chile; P. lineabasalis, new species, from Chile; P. keelioides, new species, from Chile; P. simplex, new species, from Chile; P. crocoptycha (Meyrick), new combination, from Argentina and Chile; P. wilkinsoni (Butler), new combination, from Chile; and P. galenia (Razowski), new combination, from Chile. We present brief diagnoses for the related genera Apotomops Powell and Obraztsov, Bonagota Razowski, Haemateulia Razowski, and Acmanthina Brown, along with descriptions of two new species of Apotomops (A. boliviana and A. spomotopa, new species). We also propose two new combinations, Apotomops carchicola (Razowski and Becker) and A. sololana (Razowski), and the synonymy of Bonagota cranaodes (Meyrick) with B. salubricola (Meyrick).